CARBONATIZATION AND SILICIFICATION OF PERIDOTITES WITHIN THE VEZIRLER OPHIOLITIC MÉLANGE (KULAMANISA, WESTERN TÜRKIYE): A NATURAL ANALOGUE FOR CO2 SEQUESTRATION - Akbulut, Mehmet; Tokcaer, Murat; Büçkün, Zeynep (Ofioliti, 2024)
This study presents a detailed mineralogical description of carbonatization and silicification products derived from a serpentinite outcrop within the Vezirler ophiolitic mélange near Kula (Manisa, Western Türkiye). The investigated outcrop displays a significant alteration profile from bottom to top, including carbonatized and silicified serpentinite (CS-Srp), a coalesced carbonate nodule zone (Cnz), and an iron-oxide stained silica-carbonate alteration crust (Fscc). The blackish green to green coloured, very slightly carbonatized or non-carbonatized parts of the serpentinite is mainly made of serpentine polymorphs, bastite transformed orthopyroxene, chromite, iron-oxides, and andradite. Minor carbonatization is observed with dolomite and hematite-bearing coronas around andradite in contact with serpentine. In contrast, CS-Srp comprises hydromagnesite-hydrotalcite nodules within a greenish-gray serpentinite matrix. Near the Cnz contact, discrete magnesite nodules are present, while the Cnz consists of agglomerated magnesite nodules. Fscc above the Cnz, contains magnesite nodules and dolomite-silica stockwork in the lower segment and only dolomite-silica stockwork in the upper segment. The rhythmically zoned magnesites suggest changing reactant phases during carbonatization influenced by temperature, Si solubility, XCO2, reactive surface area, and water/rock ratio. Tectonic control is indicated by the contact between Fscc and Cnz, suggesting a roughly N60W strike and a low-angle NE dipping trend (< 10°). The minimal presence of Ca-bearing minerals in the alteration paragenesis suggests Ca-deficient protoliths and metasomatizing fluids. The co-existence of magnesite and hydromagnesite-hydrotalcite at the same outcrop is attibuted to shifting pH of the metasomatizing fluid, percolation through the serpentinite and conductive cooling. Various factors, including reactant phase abundance and fluid nature likely influenced the final alteration mineralogy, providing insight into surface/near-surface transformations expected in CO2 storage projects in peridotite terranes.